PENINGKATAN AKUNTABILITAS, TRANSPARANSI DAN MANAJEMEN MELALUI MODEL AUDIT DANA RUMAH SAKIT UNTUK PENGUATAN PENGELOLAAN KEUANGAN RUMAH SAKIT - Lilis Sulistyani; Mulyadi .; Eko Madyo Sutanto (STIE AUB Surakarta, 2014)
Research subjects in this study is the head of accounting / finance , treasurer of the local government hospital financial managers and team members of local government hospital in Surakarta . This research is a qualitative descriptive study will describe the Hospital fund management area and explore the issues contained in the administration of the program and designing a model of internal audit for the financial management of the funds of Local Government Hospital. The results of the analysis of strengths and weaknesses SPI viewed from two aspects: transparency and accountability can be drawn a conclusion that most hospitals already transparent over the financial management of the Hospital Fund , however, there are still 26 % of respondents are less transparent and the transparency of the new partial answer 16%. The accountability aspect of the management of the Hospital Fund is not maximized . This is evidenced by the results of the questionnaire is only 51%, who answered yes when answering questions grains towards accountability. Based on the research findings of the audit program models created can be carried out in accordance with No. Permendagri . 61 th , 2007 and regulations Public Service Board ( BLUD ) in the Ministry of the Interior . Keywords : Accountability , Transparency , Internal Control System , Model Audit Fund